Interdisciplinary Analysis of Human Concepts and Their Implications on Islamic Education - Haryanto, Sri (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2022)
This research describes human existence in various scientific studies; psychological, physiological, spiritualist (interdisciplinary) which has an integral value to the human role in Islamic education. This research is library research, using the Koran and hadith as primary sources to explore the strong relationship between humans as nature and Islamic education. The significance of this research lies in an interdisciplinary study in revealing human nature, both in terms of psychology and sociology in the context of Islamic education. The research method used is descriptive qualitative with a library model. To deepen the study, the approach used is hermeneutics. The findings of this study are first, from psychological analysis, humans are objects as well as subjects in education, so the formulation, objectives, materials, methods, curriculum, and evaluation of education must be based on an understanding of humans within the framework of essence and existence which cannot be separated from its substance. Second, physiologically, humans are chosen beings, semi-celestial and semi-earthly creatures in which the recognition of a supernatural (God) is embedded, beings who have freedom, have a sense of responsibility towards themselves and nature. Third, spiritually, humans besides having a material physical dimension also have a spiritual dimension. In addition to being created from the essence of soil, humans were also created from the breath of God's spirit, to carry out dual duties as servants (abd), as well as God's ambassadors on earth (khalifa fil ardh).